Keabsahan Pembuktian Keterangan Saksi Melalui Media Teleconference Dalam Hukum Acara di Indonesia - Ervanda, Vivi Amelia; Soponyono, Eko (UNIB Press, 2020)
The teleconference emerged as a new legal discovery in the field of proof which was used in the event that the witness gave his testimony in the trial, but the Criminal Law Book as a legal umbrella in the court had not yet been regulated. Law Number 11 Year 2008 concerning Information and Electronic Transactions regulates electronic documents and electronic information as valid evidence which is an extension of the evidence set out in the Criminal Procedure Code. When viewed based on the understanding of electronic documents, teleconference is part of electronic documents, so indirectly, Law Number 11 Year 2008 on Information and Electronic Transactions states that teleconferences are evidence that can be used in substantiation at court, but this is contrary to Article 185 of the Criminal Procedure Code which states that witness testimony as evidence is what the witness stated at the hearing. The urgency of this research is because there are no provisions governing Teleconference as legal evidence so there is no legal certainty.Keywords: Electronic Evidence; Legitimacy; Teleconference.AbstrakTeleconference muncul sebagai penemuan hukum baru dalam bidang pembuktian yang digunakan dalam hal saksi memberikan keterangannya dalam persidangan, namun Kitab Undang-Undang Hukum Acara Pidana sebagai payung hukum bercara di persidangan belum mengaturnya. Undang-Undang Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik mengatur mengenai dokumen elektronik dan informasi elektronik merupakan alat bukti sah yang merupakan perluasan dari alat bukti yang diatur dalam Kitab Undang-Undang Hukum Acara Pidana. Apabila dilihat berdasarkan pengertian dokumen elektronik, teleconference merupakan bagian dari dokumen elektronik, sehingga secara tidak langsung, Undang-Undang Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik menyatakan bahwa teleconference merupakan alat bukti yang dapat digunakan dalam pembuktian di persidangan, namun hal ini betentangan dengan Pasal Pasal 185 KUHAP yang menyatakan bahwa, keterangan saksi sebagai alat bukti ialah apa yang saksi nyatakan didalam persidangan.Kata kunci: Alat Bukti Elektronik; Keabsahan; Teleconference